Urban Transit in Montreal: The Last Hundred Years, 1861-1961 - Montreal Urban Community Transit Commission (The Commission, 1970)
Keywords: Autobus; Tramways; Transport en commun

Inventaire archéologique des rues et des réseaux souterrains de Montréal, BjFj-50, rue place D'Youville Nord, 1989-1990 - Véronneau, François; Société d'archéologie et de numismatique de Montréal (Ministère des affaires culturelles du Québec et Ville de Montréal, 1991)
Keywords: Aqueduc; Fortifications; Places publiques; Rues; Youville (place d'); Égouts; Électricité

Inventaire archéologique des rues et des réseaux souterrains de Montréal 1989, BjFj-50, rues de la Commune, Place d'Youville Sud, Saint-Paul et Saint-Amable - Véronneau, François; Société d'archéologie et de numismatique de Montréal (Ministère des affaires culturelles du Québec et Ville de Montréal, 1990)
Keywords: Aqueduc; Marchés; Places publiques; Rues; Youville (place d'); Égouts; Électricité

La Commission du Havre de Montréal (1850-1896) - Brouillard, Pierre (Montréal: artisans, histoire et patrimoine, 1979)
Keywords: Commission du Havre; Port

Tramway à Montréal-1861 à 1959 - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
Keywords: Montreal Street Railway Company; Tramways

The Montreal Economy during the Nineteenth Century - Fougères, Dany; Labrecque, Annie-Claude (Montreal: The History of A North American City, 2018)
Keywords: Assurance; Banques; Chaussure; Chemins de fer; Lachine (canal); Montreal Board of Trade; Métropole; Port; Routes; Textile; Voie maritime

A Brief History of the Montreal Street Railway Company From 1861 to 1910 (Annual Report of the Montreal Street Railway Company For the Fiscal Year Ended 30th September 1910, 1910)
Keywords: Montreal Street Railway Company; Tramways

The Railways of Montreal - Frost, David B. (Montreal Geographical Essays, 1981)
Keywords: Chemins de fer

De 1800 à 1830. Montréal, jeune métropole britannique - Robert, Jean-Claude (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Métropole; Port

Montréal, notre île - Les passages d'eau à la fin du XVIIIe siècle - Faribault-Beauregard, Marthe (Montréal: activités, habitants, quartiers, 1984)
Keywords: Bacs

1800 to 1830. Montréal, Building British Metropolis - Robert, Jean-Claude (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne’s Market and the Parliament of the Province of Canada, 2021)
Keywords: Métropole; Port

94 ans après la Conquête un premier navire français à Montréal - Gaudet, Sylvain (Montréal en tête, 2006)
Keywords: Commerce de détail; Marchands; Port

Au Vieux-Port de Montréal - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Port; Vieux-port

Le port de Montréal, hier et aujourd'hui - Brouillette, Benoît (Revue de Géographie de Montréal, 1967)
Keywords: Port

Histoire des communautés noires au Québec et à Montréal (2e partie) - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Chemins de fer; Musique; Noirs; Travail

Montréal, par ponts et traverses - Wilson, Pierre; Poussart, Annick (Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 1999)
Keywords: Ponts

Montréal, by Bridge and Crossing - Wilson, Pierre; Poussart, Annick (Pointe-à-Callière (musée d'archéologie et d'histoire de Montréal), 1999)
Keywords: Ponts

The Montreal & Lachine Rail Road and its Successors - Bales, Robert G. (Canadian Rail, 1966)
Keywords: Chemins de fer; Montreal and Lachine Rail Road

L'importance des infrastructures de transport - Hanna, David B. (Montréal métropole, 1880-1930, 1998)

Le Pont Victoria. Le lien vital - Kennell, Elizabeth H. (Montréal, une histoire à suivre, 1992)
Keywords: Ponts; Victoria (pont)

Victoria Bridge. The Vital Link - Kennell, Elizabeth H. (Montreal, a History to Treasure, 1992)
Keywords: Ponts; Victoria (pont)

Colonisation, commerce et économie locale - Stewart, Alan (Montréal, ville fortifiée au XVIIIe siècle, 1992)
Keywords: Fortifications; Fourrure; Rues

Georges-Étienne Cartier: le saint-patron des affairistes - Germain, Jean-Claude (Montréal en tête, 2016)
Keywords: Avocats; Cartier, Georges-Étienne; Chemins de fer; Grand Tronc

Réseau routier et développement urbain dans l'île de Montréal au XIXe siècle - Robert, Jean-Claude (Barcelona-Montréal: desarrollo urbano comparado / développement urbain comparé, 1998)
Keywords: Routes

Settlement, Commerce, and the Local Economy - Stewart, Alan (Opening the Gates of Eighteenth-Century Montréal, 1992)
Keywords: Fortifications; Fourrure; Rues

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

Au canal de Lachine - Desjardins, Pauline (Lumières sous la ville. Quand l'archéologie raconte Montréal, 2016)
Keywords: Lachine (canal); Navigation

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation

Travaux d'aménagement du Havre de Montréal 1830-1850 (étude préliminaire) (Groupe de recherche sur l'histoire du port de Montréal, 1982)
Keywords: Port

Ponts et traverses de la rivière des Prairies - Tessier, Stéphane (Il était une fois... Montréal-Nord, 2020)
Keywords: Ponts; Rivière des Prairies; Rivière-des-Prairies

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
Keywords: Navigation; Rivière des Prairies

Le boulevard Saint-Laurent et son histoire - Tessier, Stéphane (Il était un fois... Montréal Nord, 2022)
Keywords: Routes; Saint-Laurent (rue)

Le transport urbain à Montréal, 1861-1961 (Commission de transport, 1961)
Keywords: Tramways; Transport en commun

En rade: marins à Montréal (1851-1896) - Bélisle-Desmeules, David (Domaine histoire, 2019)
Keywords: Navigation; Port; Travail; Vieux-port

Montréal portuaire et ferroviaire : actes du 5e congrès de l'Association québécoise pour le patrimoine industriel, Montréal, 8 et 9 mai 1992 - Association québécoise pour le patrimoine industriel (L'Association, 1993)
Keywords: Chemins de fer; Port

Montreal Port Annual. Centenary Souvenir and Reference 100 Years of Progress (Shipping Register, 1930)
Keywords: Port

Original Acquisition of Land in Montreal by the Grand Trunk Railway of Canada - Hoskins, F. H. (Université Mc Gill, Département de géographie, 1987)
Keywords: Grand Tronc; Pointe-Saint-Charles; Quartiers

Revealing new dynamics in the industrial city : a study of human/horse relations in Montreal's public space, 1860-1916 - Paulin, Catherine (Université de Montréal, 2017)
Keywords: Chevaux; Mont-Royal (parc)

John Richardson et la construction du canal de Lachine - Laliberté, Pierre (Cahier de la Société historique de Montréal, 1983)
Keywords: Lachine (canal); Navigation; Richardson, John

Le développement du port de Montréal, 1850-1896 - Brouillard, Pierre (Université du Québec à Montréal, 1976)
Keywords: Port

L'évolution des trains de banlieue montréalais: 170 ans de service (1847-2017) - Barrieau, Pierre (Université du Québec à Montréal, 2019)
Keywords: Chemins de fer; Gares; Transport en commun

L'encadrement juridique des infrastructures et des services publics urbains: le cas du transport en commun à Montréal, 1860-1880 - Fougères, Dany (Université du Québec à Montréal, 1991)
Keywords: Tramways; Transport en commun

Le Plateau sur ses grands chevaux (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2016)
Keywords: Chasse à courre; Chevaux; Clubs; Montreal Hunt Club; Tramways; Transport en commun

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Tramways de Montréal / Streetcars of Montreal - Angus, Fred F.; Irwin Wilson, Olive (Musée ferroviaire canadien de Delson/St-Constant, 1995)
Keywords: Tramways; Transport en commun

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Montreal Railway Terminals - Leduc, Michael (Michael Leduc, 2008)
Keywords: Canadien National; Canadien Pacifique; Chemins de fer; Gares

Montreal's First Railway - Leduc, Michael (Michael Leduc, 2013)
Keywords: Canadien Pacifique; Chemins de fer

The Harbour of Montreal, an Address to the St. James Literary Society of Montreal - Tombs, G. (s.é., 1952)
Keywords: Port

The Montreal Ship Channel, 1805-1865 - Corley, Nora (Université McGill, 1961)
Keywords: Navigation

Luther Holton: Mid-Century Montreal Railwayman - Klassen, Henry C. (Revue de l'Université d'Ottawa / University of Ottawa Quarterly, 1982)
Keywords: Chemins de fer; Holton, Luther Hamilton

Montreal Island Railway Stations: CN & Constituent Companies - Leduc, Michael (Michael Leduc, 1994)
Keywords: Canadien National; Chemins de fer; Gares

Montreal Island Railway Stations: CP & Constituent Companies - Leduc, Michael (Michael Leduc, 1996)
Keywords: Canadien Pacifique; Chemins de fer; Gares

Redimensioning Montreal: Circulation and Urban Form, 1846-1918 - Gilliland, Jason A. (Université McGill, 2001)
Keywords: Incendies; Port; Rues

The Port of Montreal: Its History and Development - Cowie, F. W. (Shipping Register, 1925)
Keywords: Port

Les Télécommunications à Montréal entre 1846 et 1946 - Canuel, Alain (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 1992)
Keywords: Bell Canada; Téléphone

Le réseau ferroviaire du Canadien Pacifique à Montréal - Bur, Justin (Bulletin de l'Association québécoise pour le patrimoine industriel, 2017)
Keywords: Canadien Pacifique; Chemins de fer; Gare Viger; Gare Windsor; Gares

Railways and the Urban Soundscape: Montreal, 1850s-1950s - Rudy, Jarrett; Fahrni, Magda; Kenny, Nicolas (Urban History Review / Revue d'histoire urbaine, 2022)
Keywords: Chemins de fer; Paysages

Montréal et la catastrophe du pont ferroviaire de Beloeil - Saint-Jacques, Roger (Les cahiers d'histoire de la Société d'histoire de Beloeil, 1985)
Keywords: Chemins de fer; Ponts

Relier Québec et Montréal par le chemin du Roy - Robichaud, Léon (Cap-aux-Diamants, 2012)
Keywords: Routes

On and Off the Island of Montreal, 1815-1867: The Transport Background of Town-Country Relations in the Plat Pays of Montréal - Willis, John (Espace et culture, 1995)
Keywords: Ponts; Routes

Montréal et ses voies de circulation: un mariage de raison - Marsan, Jean-Claude (Continuité, 1994)
Keywords: Autoroutes; Routes

The Urban Horse and the Shaping of Montreal, 1840–1914 - Olson, Sherry (Animal Metropolis: Histories of Human-Animal Relations in Urban Canada, 2017)

Muddy Shore to Modern Port: Redimensioning the Montréal Waterfront Time-Space - Gilliland, Jason A. (The Canadian Geographer / Le Géographe canadien, 2004)
Keywords: Paysages; Port

Connaître et valoriser le patrimoine portuaire de Montréal: un chantier inachevé - Gelly, Alain (Histoire et patrimoine. Pistes de recherche et de mise en valeur, 2019)
Keywords: Histoire; Lachine (canal); Patrimoine; Port; Vieux-port

Les p'tits chars: évolution historique du transport en commun à Montréal - Courcy-Legros, Louiselle (L. Courcy-Legros, 1985)
Keywords: Tramways; Transport en commun

Montréal et les débuts de la navigation à vapeur sur le St-Laurent - Dubuc, Alfred (Revue d'histoire économique et sociale, 1967)
Keywords: Molson (famille); Navigation

Montréal et les débuts de la navigation à vapeur sur le Saint-Laurent - Dubuc, Alfred (La grande mouvance, 1990)
Keywords: Molson (famille); Navigation; Voie maritime

Steam or Water Power? Thomas C. Keefer and the Engineers Discuss the Montreal Waterworks in 1852 - Ross, Susan M. (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Aqueduc; Énergie hydraulique

Building landscape narratives: the material and visual culture of bridge construction in Montreal, 1854-1930 - Braiden, Heather (Université McGill, 2021)
Keywords: Ponts; Victoria (pont)

The North-Shore railways: a Study of the Montreal Colonization Railroad and the North Shore Railway, 1854-1885 - Young, Brian (Queen's University, 1972)
Keywords: Canadien Pacifique; Chemins de fer; Grand Tronc

A Precipitous Decline, Steam as a Motive Power in Montreal : A Case Study of the Lachine Canal Industries - Gelly, Alain (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Lachine (canal); Énergie hydraulique

Programme d'inventaire archéologique de la Pointe-des-Seigneurs - Société d'archéomatique Chronogramme-Lauverbec (Société d'archéomatique Chronogramme-Lauverbec, 2002)
Keywords: Artisans; Confection; Fer et acier; Lachine (canal); Meunerie; Mouleurs; Ogilvie Flour Mills; Énergie hydraulique

De la voile à la vapeur: la construction des navires dans les environs de Québec et de Montréal / From Sail to Steam (...) - Baker, Victoria A.; Dutton, Diana (Musée Marsil de Saint-Lambert / Marsil Museum of Saint-Lambert, 1982)
Keywords: Construction navale; Navigation

Les services urbains sous surveillance politique: le pouvoir municipal et l'établissement du service de transport en commun à Montréal, 1860-1880 - Fougères, Dany (Urban History Review / Revue d'histoire urbaine, 1997)
Keywords: Transport en commun

The Changing Character of Streets in Central Areas with Special Reference to Sherbrooke Street as a Principal Street in City of Montreal-Canada - Rege, Ratan M. (Université McGill, 1966)
Keywords: Rues; Sherbrooke (rue)

À la belle époque des tramways - Pharand, Jacques (Éditions de l'Homme, 1997)
Keywords: Tramways; Transport en commun

Le Saint-Laurent. Grande porte de l'Amérique - Lasserre, Jean-Claude (Hurtubise HMH, 1980)
Keywords: Navigation; Voie maritime

Le Pont Victoria, un lien vital / Victoria Bridge, the vital link - Triggs, Stanley (Musée McCord d'histoire canadienne, 1992)
Keywords: Ponts; Victoria (pont)

Le Pont / The Bridge - Triggs, Stanley G. (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Le Cadre / The Setting - Young, Brian (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'inauguration / The Celebration - Graham, Conrad (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

L'impact / The Impact - Lauzon, Gilles (Le Pont Victoria, un lien vital / Victoria Bridge, the vital link, 1992)
Keywords: Ponts; Victoria (pont)

Canada and the Grand Trunk, 1829-1924: The Genesis of Railway Construction in British America and the Story of The Grand Trunk Railway Company of Canada from its Inception to its Acquisition by Canada - Lovett, H.A. (s.é., 1927)
Keywords: Chemins de fer; Grand Tronc

L'histoire du CN - MacKay, Donald (Éditions de l'Homme, 1992)
Keywords: Canadien National; Chemins de fer

Québec en Amérique au XIXe siècle. Essai sur les caractères économiques de la laurentie - Faucher, Albert (Fides, 1973)
Keywords: Port

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

Les Irlandais et le canal de Lachine. La grève de 1843 - Boily, Raymond (Leméac, 2011)
Keywords: Grèves; Irlandais; Lachine (canal)

L'organisation spatiale du corridor du Canal de Lachine au 19e siècle - Desjardins, Pauline (Université de Montréal, 1999)
Keywords: Lachine (canal)

Le développement du réseau pionnier des chemins de fer au Canada: isolement et intégration (1836-1883) - Lemaire, Marc (Université de Montréal, 1997)
Keywords: Chemins de fer

La navigation à vapeur sur le Saint-Laurent - Baker, Victoria A. (De la voile à la vapeur: la construction de navires dans les environs de Québec et de Montréal / From Sail to Steam (...), 1982)
Keywords: Navigation; Port; Voie maritime

À la croisée des chemins : mise en place et implantation du réseau de télégraphe électrique canadien, 1846-1867 - Dumais-Gingras, Pierre (Université du Québec à Montréal, 2021)
Keywords: Téléphone

Gare Dalhousie. Rapport historique et architectural - Hallé, Jacqueline (Société immobilière du patrimoine architectural de Montréal (SIMPA), 1985)
Keywords: Gares